Analisis Dampak Bulan Ramadhan Dalam Peningkatan Pendapatan Usaha Mikro Di Kelurahan Harjosari Kecamatan Medan Amplas - Ilham Wahyudi; Zuhrinal M. Nawawi; Wahyu Syarvina (LPPM Universitas Labuhanbatu, 2023)
In general, in the month of Ramadan, Muslims focus on themselvesTo do more worship, to hold thirst and hunger, automaticallyShould have reduced consumption needs, but in fact, it isIn the month of Ramadan the need and consumption increases. The purpose of the researchThis is to find out the results of the analysis of the impact of the month of Ramadan inIncrease in the income of micro businesses in the Harjosari sub-districtSandpaper Field. This research is a qualitative descriptive study. WithUsing data collection techniques through interviews, observation, andDocumentation. The results of this study indicate that there is a positive impactOn increasing micro business income in the Harjosari sub-districtMedan Sandpaper, due to increased consumption patterns of society inMonth of Ramadan, which causes an increase in business incomeMicro, due to the increasing need of the community to shop for needsFood or drink to eat when breaking the fast. As well as impactNegative consequences arising from increased consumption patterns, namely potentialEmergence of extravagance and wastefulness. And the factor of opening hours becomes a problemAgainst several micro entrepreneurs.